1998
DOI: 10.1074/jbc.273.8.4734
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Approaches to Define the Functional Role of Dual Site Phospholamban Phosphorylation

Abstract: Phospholamban is a critical regulator of the sarcoplasmic reticulum Ca 2؉ -ATPase activity and myocardial contractility. Phosphorylation of phospholamban occurs on both Ser 16 and Thr 17 during isoproterenol stimulation. To determine the physiological significance of dual site phospholamban phosphorylation, we generated transgenic models expressing either wild-type or the Ser 16 3 Ala mutant phospholamban in the cardiac compartment of the phospholamban knockout mice. Transgenic lines with similar levels of mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
80
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 29 publications
6
80
0
2
Order By: Relevance
“…Although the detailed mechanism of this process is not understood, a current view is that in the unphosphorylated form PLB interacts with SERCA and inhibits pumping activity, possibly by reducing its affinity for calcium ions (compare [11] with [12,13]), and reducing the maximum turnover rate at saturating calcium ion concentration, which is reflected in the Ca/MgATPase activity rate (reviewed in [14,15]). Phosphorylation of Ser16 of PLB by cAMP or cGMP dependent protein kinases and/or phosphorylation of Thr17 by the multifunctional calmodulin dependent protein kinase [16,17] results in increased activity of the pump [18,19].The detailed mechanism by which PLB modulates the activity of the calcium pump is far from clear as the experimental findings of different investigators have not always been consistent (see [17,20] for discussion on this point). The fact that the sequence of PLB comprises two distinctive domains (an N-terminal hydrophilic region, residues 1±31, presumed to be cytoplasmic, and a C-terminal hydrophobic transmembrane region, residues 32±52), implies that the functional roles of these two domains in the interaction of PLB with the calcium pump are different.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Although the detailed mechanism of this process is not understood, a current view is that in the unphosphorylated form PLB interacts with SERCA and inhibits pumping activity, possibly by reducing its affinity for calcium ions (compare [11] with [12,13]), and reducing the maximum turnover rate at saturating calcium ion concentration, which is reflected in the Ca/MgATPase activity rate (reviewed in [14,15]). Phosphorylation of Ser16 of PLB by cAMP or cGMP dependent protein kinases and/or phosphorylation of Thr17 by the multifunctional calmodulin dependent protein kinase [16,17] results in increased activity of the pump [18,19].The detailed mechanism by which PLB modulates the activity of the calcium pump is far from clear as the experimental findings of different investigators have not always been consistent (see [17,20] for discussion on this point). The fact that the sequence of PLB comprises two distinctive domains (an N-terminal hydrophilic region, residues 1±31, presumed to be cytoplasmic, and a C-terminal hydrophobic transmembrane region, residues 32±52), implies that the functional roles of these two domains in the interaction of PLB with the calcium pump are different.…”
mentioning
confidence: 97%
“…The detailed mechanism by which PLB modulates the activity of the calcium pump is far from clear as the experimental findings of different investigators have not always been consistent (see [17,20] for discussion on this point). The fact that the sequence of PLB comprises two distinctive domains (an N-terminal hydrophilic region, residues 1±31, presumed to be cytoplasmic, and a C-terminal hydrophobic transmembrane region, residues 32±52), implies that the functional roles of these two domains in the interaction of PLB with the calcium pump are different.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under physiological conditions, PLN phosphorylation at Ser-16 by PKA is the predominant event so far described that leads to proportional increases in the rate of Ca 2ϩ uptake into SR and accelerates ventricular relaxation (40,41). DMPK phosphorylation of Ser-16-PLN emerges as a novel mechanism involved in the regulation of cardiac contractility that may be therapeutically relevant because of the preferential muscular expression pattern of DMPK.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested an interaction between the PKA and CaMKII pathways for PLN phosphorylation. The availability of transgenic models expressing wild-type PLN (PLN-WT), the Ser 16 →Ala mutant PLN (PLN-S16A) or the Thr 17 →Ala mutant PLN (PLN-T17A) in the cardiac compartment of PLN knock-out mice, and of phosphorylation sitespecific antibodies to PLN, which precisely discriminate between the Ser 16 and the Thr 17 phosphorylation sites, in combination with the quantification of 32 P incorporation into PLN, helped to clarify the relative role of Ser 16 and Thr 17 phosphorylation (9,13,14). Experiments in transgenic mice expressing either PLN-WT or the PLN-S16A, indicated that the phosphorylation of Ser 16 of PLN is a prerequisite for the phosphorylation of Thr 17 (13).…”
Section: Role Of the Phosphorylation Of Thr 17 Of Pln During ß-Adrenementioning
confidence: 99%